Assessment of risk factors for suicidal behavior: results from the Tehran University of Medical Sciences Employees' Cohort study - Rezaei, Zahed; Mohammadi, Samira; Aghaei, Abbas; Pouragha, Hamidreza; Latifi, Arman; Keshavarz-Mohammadi, Nastaran (Frontiers in Public Health, 2023)
Introduction: Suicide is a major issue of concern for public health. It is estimated that suicide accounts for 700 000 deaths every year. A personal history of one or more attempted suicide is the most important determinant of suicide among the general population. This study aims to assess the major risk factors associated with suicide behaviors among Iranian employees in medical setting.In this studythis study, 3913 employees of Tehran University of Medical Sciences employees participating in the university's employeesemployee's cohort study were recruited.Suicidal behaviors (SB) and their associated risk factors were evaluated using the World Mental Health Composite International Diagnostic Interview (CIDI) Version 3.0. Univariate and multivariate logistic regressions were performed to identify the determinants of suicidal behaviorsSB among the participants, and the crude and adjusted odds ratios (ORs) with corresponding 95% confidence interval (95% CI) were calculated.Results: 49.6 % (n=1939) of respondents reported that they were tired of life and thinking about death. The lifetime prevalence rates of suicidal ideation (SI) were 8.1% (n = 317), suicide plans (SP) 7.3% (n = 287) and suicide attempts (SA) 3.1%, (n = 122). Being women (OR:1.87,